USE OF INTEGRATED TEACHING METHODOLOGY IN ELEMENTARY STUDENTS - Joniqulova Zulayxo; Yo‘ldosheva Shohista (Web of Journals Publishing, 2024)
In this article, the methods of interdisciplinary communication as a factor of increasing student activity, the methods of using the integrated teaching method in elementary school students, problems and solutions, and suggestions are described.
Keywords: Interdisciplinary relations, integration, integration, cognitive capacity, education, tool, textbook, Irish school, foreign experience.